Clinical management of patients with breast cancer-related lymphedema: a best practice implementation project. Issue 3 (8th September 2020) - Zhao, Huihui; Zhou, Chunlan; Wu, Yanni; Li, Wenji; Li, Xiaojin; Chen, Liling
ABSTRACT: Background and aims: Breast cancer-related lymphedema (BCRL) is a burdensome complication of breast cancer that may significantly affect patients' quality of life. Best evidence-based interventions should be applied to the clinical management of BCRL to provide the best care for patients. This project aimed to promote evidence-based practices in the management of patients with BCRL and to assess the impact of these changes on improving clinical outcomes in a large tertiary hospital. Methods: The current evidence implementation project was conducted in the Breast Surgery Department of a tertiary hospital in China. Four audit criteria were developed for the baseline and follow-up audits. The project used the JBI Practical Application of Clinical Evidence System and the Getting Research into Practice audit and feedback tool to promote evidence-based healthcare into practice. Twenty patients with BCRL were assessed both in baseline and follow-up audits. Results: The results of the baseline audit demonstrated that there was poor compliance with most of the audit criteria. Significant improvements were achieved in the four audit criteria in the follow-up audit compared with those in the baseline audit. The 55% of women with BCRL being offered complex decongestive therapy rose from 25 to 55%. Individualized exercise program implementation increased from 50% at baseline to 90% at follow-up. Compliance with resistance training being provided improved from 0 to 90%. Education of patients improved, with specific education about the benefits of exercise in the management of lymphedema increasing from 75 to 100%. Conclusion: The current evidence-based implementation project for the clinical management of patients with BCRL was successfully conducted. However, patient outcomes and the sustainability of the audit criteria were not evaluated, which are needed in further studies.